1983
DOI: 10.1002/cne.902190403
|View full text |Cite
|
Sign up to set email alerts
|

The relation of corpus callosum connections to architectonic fields and body surface maps in sensorimotor cortex of new and old world monkeys

Abstract: Corpus callosum connections of parietal and motor cortex were studied in New World owl monkeys (Aotus trivirgatus) and Old World macaque monkeys (Macaca fascicularis) after multiple injections of 3H-proline and horseradish peroxidase, HRP, into one cerebral hemisphere, and extensive microelectrode mapping of architectonic Areas 3b, 1, and 2 of the other hemisphere. Results were obtained both from parasagittal brain sections cut orthogonal to the brain surface and from sections from flattened brains cut paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(143 citation statements)
references
References 56 publications
16
121
1
1
Order By: Relevance
“…The callosal system of the superior parietal lobule has been described in detail (Caminiti and Sbriccoli, 1985) and will be reconsidered here only in relation to certain aspects of the interhemispheric transfer of motor behavior. In agreement with other studies, the pattern of frontal callosal connections that emerges from our work points up some of the main features of that transfer: the relative absence of callosal cells in part of the hand and foot representations of M 1 (Jenny, 1979;Jones et al, 1979;Killackey et al, 1983;Gould et al, 1986); the presence of callosal connections in more rostrally and laterally located frontal fields (Gould et al, 1986), in which additional representations of the arm and hand have been found (in area 6; Muakkassa and Strick, 1979;Gould et al, 1986;Matelli et al, 1986); the abundance of callosal projecting cells in the proximal limb, trunk, and face representations (Jones et al, 1979;Gould et al, 1986). This complex and fractionated pattern of callosal connections suggests a heterogeneity in the structural organization of the frontal lobe that is also evidenced by morphological studies (Matelli et al, 1986;Barbas and Pandya, 1987).…”
Section: Lack Of Bifurcated Neuronssupporting
confidence: 76%
“…The callosal system of the superior parietal lobule has been described in detail (Caminiti and Sbriccoli, 1985) and will be reconsidered here only in relation to certain aspects of the interhemispheric transfer of motor behavior. In agreement with other studies, the pattern of frontal callosal connections that emerges from our work points up some of the main features of that transfer: the relative absence of callosal cells in part of the hand and foot representations of M 1 (Jenny, 1979;Jones et al, 1979;Killackey et al, 1983;Gould et al, 1986); the presence of callosal connections in more rostrally and laterally located frontal fields (Gould et al, 1986), in which additional representations of the arm and hand have been found (in area 6; Muakkassa and Strick, 1979;Gould et al, 1986;Matelli et al, 1986); the abundance of callosal projecting cells in the proximal limb, trunk, and face representations (Jones et al, 1979;Gould et al, 1986). This complex and fractionated pattern of callosal connections suggests a heterogeneity in the structural organization of the frontal lobe that is also evidenced by morphological studies (Matelli et al, 1986;Barbas and Pandya, 1987).…”
Section: Lack Of Bifurcated Neuronssupporting
confidence: 76%
“…Anatomic tracer studies in multiple species have shown limited callosal connections between corresponding distal limb motor cortices. That somatomotor synchrony is less affected by callosotomy is consistent with the existence of these "callosal holes" (Myers, 1965;Pappas and Strick, 1981;Killackey et al, 1983). Conversely, persistent somatomotor correlations after callosotomy may be caused by synchronous ascending information transmitted via somatomotor thalamocortical projections.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to pain, tactile stimulation of the hand results in bilateral SI activation (Hansson and Brismar 1999); this was around 20% less than the contraleral effect, which was similar to that observed in our study for brush stimuli. Anatomical studies of corpus callosum connections indicated relatively sparse connections for the glabarous hand and foot compared with the face and trunk (Killackey et al 1983). Thus, in humans multiple pathways for noxious information may exist that activate bilateral regions in the cortex (Tsuji et al 2006).…”
Section: Activation In the Somatosensory Regionmentioning
confidence: 99%